Concentration and migration of heavy metals in the "tailing-soil-plant" uranium province Maili-Suu (Eurasian Journal of Ecology, 2016)
The article presents the concentration and migration of heavy metals in the "tailing-soil-plant" uranium biogeochemical province Maili-Suu, data analysis mowing plants and soils of two tailings number 3 and number 6.
Keywords: tailings; dumps; heavy metals; plants; soil; MPC; clarke